Challenges of constructing legitimacy in peacebuilding : Afghanistan, Iraq, Sierra Leone, and East Timor - Higashi, Daisaku, 1969- (London ; New York : Routledge, Taylor & Francis Group, 2015)
"The objective of this book is to develop an understanding of the mechanisms for constructing--or eroding--the legitimacy of newly created governments in post-conflict peacebuilding environments"--
Includes bibliographical references and index.
Keywords: Legitimacy of governments -- Developing countries; Peace-building -- Developing countries; International relations; POLITICAL SCIENCE / General; POLITICAL SCIENCE / History & Theory; POLITICAL SCIENCE / International Relations / General